Analysis of "Productive and Educative" Performance in the Lesson Studies of the Center of Excellence SMK (Study at State Vocational High School 4 Bandar Lampung) - Nurhayani; Sinaga, Risma Margaretha; Pujiati (International Journal of Educational and Life Sciences, 2024)
This research was carried out to determine the implementation of the teaching factory learning model and Project Base Learning in an effort to improve the productive and educational performance of grade XI students in specialization subjects at the State 4 Bandar Lampung vocational school. This research is qualitative research using data analysis techniques, namely Data Resolution, Data Presentation, Conclusion Drawing/Verification. The results of the Operational Research of the Education Unit by using the suitability of the Teaching Factory and PjBL planning models with the integration of the curriculum with each stakeholder and the appropriate assessment, the planning of the Teaching Factory and PjBL is able to improve Educational and Productive Performance. The Teaching Factory and PjBL models have a good contribution in improving the Educational and Productive Performance of Students in the Vocational School of Negeri 4 Bandar Lampung in the Department of Hospitality.